2012
DOI: 10.4049/jimmunol.1102097
|View full text |Cite
|
Sign up to set email alerts
|

The Inference of Phased Haplotypes for the Immunoglobulin H Chain V Region Gene Loci by Analysis of VDJ Gene Rearrangements

Abstract: The existence of many highly similar genes in the lymphocyte receptor gene loci makes them difficult to investigate, and the determination of phased “haplotypes” has been particularly problematic. However, V(D)J gene rearrangements provide an opportunity to infer the association of Ig genes along the chromosomes. The chromosomal distribution of H chain genes in an Ig genotype can be inferred through analysis of VDJ rearrangements in individuals who are heterozygous at points within the IGH locus. We analyzed V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
132
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(146 citation statements)
references
References 44 publications
14
132
0
Order By: Relevance
“…An intriguing possibility is that genetic changes such as insertions or deletions in noncoding regions, as well as deletions or duplications of genes (40), could change distances between VDJ gene segments, thus altering their frequencies in the repertoire. Such changes can in turn tune the composition of the set of public clonotypes in accordance with threats posed by common pathogens, and potentially also with evolving needs for self-maintenance (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing possibility is that genetic changes such as insertions or deletions in noncoding regions, as well as deletions or duplications of genes (40), could change distances between VDJ gene segments, thus altering their frequencies in the repertoire. Such changes can in turn tune the composition of the set of public clonotypes in accordance with threats posed by common pathogens, and potentially also with evolving needs for self-maintenance (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Application of this approach to the seven subjects in Table 1 found that each subject had a unique genotype, a result similar to that found in ref. 6. Most (63%) IGHV genes were homozygous, and duplications of IGHV1-69 or IGHV2-70 were found in three cases (Table S1).…”
Section: Automated Methods Detects Novel Ighv Alleles From Experimentalmentioning
confidence: 99%
“…Existing approaches for inferring Ig genotypes are based on identifying the set of alleles that appear above a specified frequency (6,19). This frequency is calculated using the set of unmutated sequences, as existing V(D)J segment identification tools are most accurate at identifying and aligning these sequences to their germline sequences (2).…”
Section: Automated Methods Detects Novel Ighv Alleles From Experimentalmentioning
confidence: 99%
See 2 more Smart Citations